DESENVOLVIMENTO DE PROTOCOLO PARA NUTRIZES EXTERNAS DE BANCO DE LEITE HUMANO REGIONAL DO INTERIOR DO ESTADO DO RIO GRANDE DO SUL - Lourensi, Cristiane Machado (2024)
Breastfeeding is one of the vital aspects of maternal and child health, offering a series of essential benefits to mothers and children. Thus, for hospitalized children who are unable to breastfeed directly, Human Milk Banks are a fundamental strategy for promoting and supporting breastfeeding, aligned with the Sustainable Development Goals of the World Health Organization in the Health and Well-being axis. Objectives: To map the care provided to external nursing mothers in a Human Milk Bank to consolidate a service protocol and to develop a service protocol for the care provided to external nursing mothers in a Human Milk Bank of a public hospital in the interior of Rio Grande do Sul. Methodological approach: It is configured as a Scoping review. For this review, the Problem, Concept and Context (PCC) strategy was listed to guide data collection through the following question: What are the care provided to external nursing mothers in a Human Milk Bank listed in scientific publications that are relevant to the consolidation of a service protocol? The search for evidence was carried out in Scielo, Lilacs and Pubmed databases based on eligibility criteria, and the data were analyzed descriptively. For technical/technological production, the following steps were followed: Purpose, Justification, Scope, Intervention, Operational Process, Indicators (monitoring). After the formulation, layout and review of the protocol by the researcher, it will be forwarded to a professional with expertise in the area of breastfeeding for final review. Results: seven studies were eligible for the scope review, which highlighted nursing consultations, guidelines and protocols, standard operating procedures and aspects related to infrastructure such as management care that allow nursing mothers to donate human milk safely. In addition, it was possible to map care related to the donated milk itself, corroborating the practices of pasteurization, storage and screening of milk, both pre and post-pasteurization of donations, and microbiota testing, donor screening and motivation of donors for this donation process were care that stood out in the studies found. Technical/technological product and its applicability: the care protocol for nursing mothers external to a human milk bank is configured as a technical production that encourages breastfeeding. It will contribute to care strategies and the work process, and can be used in other scenarios similar to the one proposed. In this way, it presents replicability and potential impact in the short and medium term by consolidating and systematizing a health practice. Conclusions: It is believed that the product developed in this dissertation has the potential to direct inter- and multi-professional practice in the care of external donors through access to quality care based on the best scientific evidence.